2016
DOI: 10.1016/j.jglr.2015.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Invasive species sustain double-crested cormorants in southern Lake Michigan

Abstract: Double-crested cormorants (Phalacrocorax auritus) have long and often been implicated in having detrimental effects on fisheries. Resulting persecution, as well as DDT water contamination, led to a major decline of the species throughout its range. Research shows that the main components of cormorant diets vary significantly among forage, invasive, or economically important fish species. A recent, rapid increase in cormorant abundance in the Great Lakes has led, in some instances, to calls for the management o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
3
2
0
Order By: Relevance
“…aethiopicus and C. gariepinus , which currently constitute a higher proportion of fish landings, are too large for the birds to swallow. This suggestion corroborates well with the observations by Madula and Jones (2016) who reported in their study on invasive species sustaining double‐crested cormorants in southern Lake Michigan that small‐bodied invasive fish species such as round goby ( Neogobius melanostomus ), white perch ( Morone Americana ) and alewife ( Alosa pseudoharengus ) constituted over 80% and 90% of the diet of cormorants by biomass and number, respectively. Thus, because of the stunted growth of O .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…aethiopicus and C. gariepinus , which currently constitute a higher proportion of fish landings, are too large for the birds to swallow. This suggestion corroborates well with the observations by Madula and Jones (2016) who reported in their study on invasive species sustaining double‐crested cormorants in southern Lake Michigan that small‐bodied invasive fish species such as round goby ( Neogobius melanostomus ), white perch ( Morone Americana ) and alewife ( Alosa pseudoharengus ) constituted over 80% and 90% of the diet of cormorants by biomass and number, respectively. Thus, because of the stunted growth of O .…”
Section: Resultssupporting
confidence: 92%
“…The birds had spread around the lake in 2015, with a new habitat of dead trees left from the flooded lake being a foraging site. While this cormorant invasion is new to Lake Baringo, this bird species is known to cause problems to various fisheries around the world (Madula & Jones, 2016). Recent observations, however, suggest a majority of the greater cormorants are exiting from Lake Baringo, possibly attributable to fishery that is less attractive as a foraging site.…”
Section: Resultsmentioning
confidence: 99%
“…The large contribution of Notropis spp. and gizzard shad (during fall) in the Saginaw Bay cormorant diets is consistent with this, and the prevalence of round goby in the diet is similar to other areas in the Great Lakes (Somers et al, 2003;Coleman et al, 2012;Johnson et al, 2010Johnson et al, , 2015aVan Guilder and Seefelt, 2013;Madura and Jones, 2016).…”
Section: Consumption Of Juvenile Fish By Cormorants Has Been Identifisupporting
confidence: 78%
“…Because Saginaw Bay is a valuable recreational and commercial fishing location , cormorants on Sportfish were not the dominant diet item by number or biomass except in April 2013 when yellow perch (almost all age-1) were the dominant component (biomass and number) of the diet at Little Charity Island and in June 2013 when walleye comprised 54% of the diet biomass at Spoils Island. Yellow perch consumption occurred mostly in April and early May, a pattern which has been found in other areas of the Great Lakes (Diana et al, 2006;Madura and Jones, 2016). However, in Saginaw Bay the consumption during early spring was not of spawning adults, but of age-1 fish.…”
Section: Discussionsupporting
confidence: 59%
“…With these data, it is possible to estimate the historical size of cormorant populations and also consider the differences in the new environment driven by increasing anthropogenic influence, which together can be used to help set informed and achievable management goals. Although paleolimnological data suggested that the current double-crested cormorant population in Lake Ontario is now more numerous than in the past ∼150 years, the large colonies are principally supported in the new environment by introduced and nuisance warm-water fish species that are growing in numbers due to climate change, such as round goby (Neogobius melanostomus) and alewife (Alosa pseudoharengus) (Madura and Jones, 2016). By preying on these warm-water fish species, it could be argued that cormorants act as a biological control that contributes to maintaining natural biodiversity and supports commercially valuable native cold-water taxa, such as lake trout (Salvelinus namaycush) and lake whitefish (Coregonus clupeaformis) (Johnson et al, 2010(Johnson et al, , 2015.…”
Section: How Have Populations Responded To Human Intrusion?mentioning
confidence: 99%